Induction Phase of Spontaneous Liver Transplant Tolerance - McCaughan, Geoffrey W.; Bowen, David G.; Bertolino, Patrick J. (Frontiers in Immunology, 2020)
The liver has long been known to possess tolerogenic properties. Early experiments in liver transplantation demonstrated that in animal models, hepatic allografts could be accepted across MHC-mismatch without the use of immunosuppression, and that transplantation of livers from the same donor was capable of inducing tolerance to other solid organs that would normally otherwise be rejected. Although this phenomenon is less pronounced in human liver transplantation, lower levels of immunosuppression are nevertheless required for graft acceptance than for other solid organs, and in a minority of individuals immunosuppression can be discontinued in the longer term. The mechanisms underlying this unique hepatic property have not yet been fully delineated, however it is clear that immunological events in the early period post-liver transplant are key to generation of hepatic allograft tolerance. Both the hepatic parenchyma and the large number of donor passenger leukocytes contained within the liver allograft have been demonstrated to contribute to the generation of donor-specific tolerance in the early post-transplant phase. In particular, the unique nature of hepatic-leukocyte interactions appears to play a crucial role in the ability of the liver to silence the recipient alloimmune response. In this review, we will summarize the evidence regarding the potential mechanisms that mediate the critical early phase in the generation of hepatic allograft tolerance